2021
DOI: 10.1021/acsomega.0c05490
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Effect of Water, Temperature, and Pressure on Methane Adsorption in Shale Gas Reservoirs

Abstract: Adsorption is one of the most important forms of storage of gas in shale reservoirs. Shale gas adsorption in the actual reservoir is not only affected by individual factors such as water content, temperature, and pressure but also by the synergetic effect of these factors. In this study, we conducted laboratory experiments on methane adsorption in dry and wet shale at different pressures and temperatures. The synergetic effect of water content, temperature, and pressure on shale gas adsorption is explored. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 107 publications
1
19
0
Order By: Relevance
“…The impact of preadsorbed water was more significant than that of water vapor. Several studies have shown that adsorbed water has a detrimental effect on supercritical methane adsorption on shales; 96,97 for example, methane sorption capacity in moisture-equilibrated shales [at 97% relative humidity (RH)] was reduced by 40−60% compared to dry samples. 12 The early work on the effect of water adsorption on methane adsorption on kerogens was based on studies of coal.…”
Section: Comparison Of Supercritical Adsorption Isobars For Kerogens ...mentioning
confidence: 99%
“…The impact of preadsorbed water was more significant than that of water vapor. Several studies have shown that adsorbed water has a detrimental effect on supercritical methane adsorption on shales; 96,97 for example, methane sorption capacity in moisture-equilibrated shales [at 97% relative humidity (RH)] was reduced by 40−60% compared to dry samples. 12 The early work on the effect of water adsorption on methane adsorption on kerogens was based on studies of coal.…”
Section: Comparison Of Supercritical Adsorption Isobars For Kerogens ...mentioning
confidence: 99%
“…Gasparik et al. , found that the methane adsorption capacity of wet shale was approximately 40–90% lower than that of dry shale. Han et al experimentally found that the higher the water content of shale, the lower its methane adsorption capacity. Some scholars studied the water vapor adsorption law by water vapor adsorption experiments under different temperature and pressure conditions, and established adsorption models. Previous experiments on water vapor adsorption have emphasized the influence of water vapor on shale gas adsorption and fluid flow capacity. However, it is controversial whether water is gaseous under formation conditions, and some studies have shown that the water phase is liquid under high-temperature and high-pressure conditions at certain burial depths .…”
Section: Introductionmentioning
confidence: 99%
“…Gasparik et al 19,20 found that the methane adsorption capacity of wet shale was approximately 40−90% lower than that of dry shale. Han et al 21 experimentally found that the higher the water content of shale, the lower its methane adsorption capacity. Some scholars studied the water vapor adsorption law by water vapor adsorption experiments under different temperature and pressure conditions, and established adsorption models.…”
Section: Introductionmentioning
confidence: 99%
“…Gas is stored in shale mainly as adsorbed gas in the organic matter and clay minerals and as free gas in the fractures and other pores. , Therefore, understanding the characterization and evaluation of adsorbed gas and free gas is greatly significant in shale gas reservoir evaluations and estimating the original gas in place. In this study, the variation in the relationship between the adsorption of methane and the free gas in shale under different pressure conditions is illustrated in Figure .…”
Section: Resultsmentioning
confidence: 99%